An ameliorative protocol for the quantification of purine 5′,8-cyclo-2′-deoxynucleosides in oxidized DNA - Terzidis, Michael A.; Chatgilialoglu, Chryssostomos (Frontiers in Chemistry, 2015)
5',8-Cyclo-2'-deoxyadenosine (cdA) and 5',8-cyclo-2'-deoxyguanosine (cdG) are lesions resulting from hydroxyl radical (HO•) attack on the 5'H of the nucleoside sugar moiety and exist in both 5'R and 5'S diastereomeric forms. Increased levels of cdA and cdG are linked to Nucleotide Excision Repair mechanism deficiency and mutagenesis. Discrepancies in the damage measurements reported over recent years indicated the weakness of the actual protocols, in particular for ensuring the quantitative release of these lesions from the DNA sample and the appropriate method for their analysis. Herein we report the detailed revision leading to a cost-effective and efficient protocol for the DNA damage measurement, consisting of the nuclease benzonase and nuclease P1 enzymatic combination for DNA digestion followed by liquid chromatography isotope dilution tandem mass spectrometry analysis.